Memaknai Bahtera Nuh dalam Kejadian 6-7 pada Konteks Isolasi Mandiri Penderita Covid-19 - Eddis Sagala (IAKN Ambon, 2022)
Self-isolation is temporary isolation in a place because of a situation that is considered dangerous. This study seeks to interpret and relate the story of Noah and his ark to the situation of Covid-19 sufferers who are in self-isolation. The research method in this study is a qualitative method through literature review, namely descriptive analysis of the book of Genesis 6-7. The research method in this study is a qualitative method through literature review, namely descriptive analysis by exegesis the book of Genesis 6-7. The findings obtained were that Noah and his extended family as well as various types of animals in the ark were the first acts of self-isolation on God's instructions because of the very dangerous conditions of the flood. Those who helped isolate themselves in the ark for 150 days to avoid the threat of the danger of a flood. Patients with Covid-19 must now self-isolate for 14 days for their personal safety and for the safety of their families and others around them. Covid-19 sufferers need support and enthusiasm from every community while undergoing independent isolation in an effort to complete recovery.AbstrakIsolasi mandiri merupakan pengasingan dalam sementara waktu di dalam sebuah tempat karena situasi yang dianggap berbahaya. Penelitian ini berupaya untuk memaknai dan merelevansikan kisah Nuh dan bahteranya kepada situasi penderita Covid-19 yang menjalani isolasi mandiri. Metode penelitian dalam penelitian ini ialah metode kualitatif melalui kajian pustaka yakni analisis deskriptif dengan mengeksegesa kitab Kejadian 6-7. Hasil temuan yang diperoleh ialah ternyata Nuh dan keluarga besarnya serta berbagai jenis binatang dalam bahtera merupakan tindakan isolasi mandiri pertama atas instruksi Tuhan karena kondisi air bah yang sangat berbahaya. Mereka yang turut mengisolasi diri dalam bahtera selama 150 hari supaya terhindar dari ancaman bahaya air bah. Para penderita Covid-19 kini juga harus melakukan isolasi mandiri selama 14 hari demi keselamatan pribadinya dan demi keselamatan keluarganya dan orang lain yang berada di sekitarnya. Penderita Covid-19 membutuhkan dukungan dan semangat dari setiap masyarakat selama menjalani isolasi mandiri dalam upaya pemulihan yang utuh.